The treatment of realia in the translations of Smagul Yelubay’s novel “Ak Boz Uy” - Manapbayeva, Zh.Zh.; Seidenova, S.D.; Kabdrgalinova, S.B.; Sarzhanova, G.B. (Journal of Language and Linguistic Studies, 2021)
The purpose of this study is to identify the types and frequency of the techniques for translating realia. Uses and misuses of various techniques have been assessed from the perspectives of domestication and foreignization on the basis of a rich corpus compiled from the Russian and English translations of Smagul Yelubay’s novel “Ak Boz Uy” in the Kazakh language. The novel contrasts the nomadic and sedentary lives of the Kazakh people, thus describing the shift from felt yurts to brick houses, camel caravans to automobiles, folk courts to Soviet prisons, from the poor men having 20 heads of cattle to the poor men begging for a slice of bread, from ideal marital life to endless divorces, from the society without orphans to orphanages. Therefore, the novel is full of culture-specific items, or so-called realia, which give cultural colour to the whole literary work. From the analysis of the achieved results, it can be concluded that along with well-known techniques discussed by various authors in the sphere of Translation Studies, procedures like cultural substitution, grammar transposition, and translation triplets can be applied to render realia. In the future we propose conducting such a corpus-based research on the treatment of extralinguistic realia, i.e. allusions, and translation of stylistic figures containing realia or references to cultural information.
Keywords: domestication; foreignization; translation errors; substitution; grammar transposition